Big Book “Aku Anak Indonesia” to Stimulate Religious Moderation in Early Childhood - Ni Luh Drajati Ekaningtyas; Ni Nyoman Sinar Widia Swari (Universitas Pendidikan Ganesha, 2023)
Cases of violence and discrimination in Indonesia are still dominated by religion-based conflicts, so it is important to internalize religious moderation from an early age. Stimulation in early childhood requires special learning media that suit their characteristics and developmental needs, one of which is a big book with attractive and colorful pictures. However, there is no big book that has been specifically developed to stimulate religious moderation for early childhood. Therefore, this study aims to develop a a valid and appropriate big book with entitled